Performance of Six- and Ten-story Reinforced Concrete Buildings Designed by using Modified Partial Capacity Design (M-PCD) Method with 70% Shear Force Ratio - Pamuda Pudjisuryadi; F. Wijaya; R. Tanuwijaya; B.C. Prasetyo; Benjamin Lumantarna (Institute of Research and Community Outreach - Petra Christian University, 2021)
One design alternative of earthquake resistant building is Partial Capacity Design (PCD) method. Unlike the commonly used capacity design method, PCD allows a safe failure mechanism which is called partial sidesway mechanism. In this mechanism, all beams and some columns are allowed to experience plastic damages while some selected columns are designed to remain elastic (called elastic columns). A new approach to predict the required strengths needed to design each structural member, called modified-PCD (M-PCD) is proposed. In this research six- and ten-story reinforced concrete buildings were designed using M-PCD, and their seismic performances are investigated. The base shear force resisted by the elastic columns was set to approximately 70% of the total base shear. Both nonlinear static procedure (NSP) and nonlinear dynamic procedure (NDP) are used to analyze the structures. The results show that the expected partial side sway mechanism is observed, and the drifts of the buildings are acceptable.